Case report: Endolymphatic system disease in elasmobranchs: clinical presentation, diagnosis, and treatment strategies - Greene, Whitney; Pereira, Nuno; Doescher, Bethany; Rojo-Solis, Carlos; David, Hugo; Faustino, Ricardo; Reese, David; De Voe, Ryan; Latson, Ed; Mylniczenko, Natalie (Frontiers in Veterinary Science, 2025)
The inner ear is an often overlooked system in elasmobranchs with few documented reports of disease or other abnormalities in the literature. Similar to terrestrial vertebrates, it is located in the cranium, and there are multiple components to the ear of elasmobranchs including a pair of membranous labyrinths each with three semicircular canals and four chambers or end organs (the saccule, the lagena, the utricle and the macula neglecta) making up the endolymphatic system (ELS). There is species variability among the inner ear anatomy of elasmobranchs, and this may play a role in disease development, progression, and treatment outcomes. Also similar to terrestrial vertebrates, this system plays a key role in hearing, acceleration, and orientation. When affected, clinical signs may include localized areas of swelling or stoma development along the dorsal midline of the head at the endolymphatic pores, atypical swimming behaviors consistent with vestibular disease (spiraling/spinning or barrel rolling, or tilting to one side), and anorexia. Less frequently, the eyes may also be affected and present with exophthalmia, hyphema, and/or panophthalmitis. Herein are case series from five institutions representing a variety of elasmobranch species affected with ELS disease with discussion of anatomy, clinical presentation, diagnostics, etiology, treatment, and outcomes. Endolymphatic disease may be clinically underdiagnosed in elasmobranchs and mistaken for other diseases such as superficial subcutaneous or subdermal abscesses, focal dermatitis, or neuropathies presumed to not be associated with the inner ear system. In addition, disease may be occult for a long period of time prior to overt manifestation of signs or chronic with waxing and waning clinical signs, likely because of anatomy and resultant treatment challenges. Awareness and additional research may help to promote timely identification, improve diagnostic and treatment options, and help to optimize individual animal welfare.